Microstructure and texture evolution during grain growth of AM30 magnesium alloy. Issue 21 (2nd November 2022) - Panda, D.; Kushwaha, R.; Sabat, R. K.; Suwas, S.; Sahoo, S. K.
ABSTRACT: AM30 magnesium alloy was subjected to annealing at temperatures ranging from 200 to 450°C for 1–1440 min to evaluate the microstructure and texture evolution during grain growth. The grain growth exponent of n = 9 and activation energy of Q = 105.6 KJ/mol were observed. Precipitates, such as Mg17 Al12, Al8 Mn5 and Al11 Mn4 were observed in the alloy, and they were found to be reduced with increasing the annealing temperature/time. The precipitates further appeared to be dissolved at a higher annealing temperature of 450°C, leading to abnormal grain growth in the alloy. The effects of solute drag and dislocation density on the grain growth behaviour, estimated through a mesoscale model based on cellular automata, were found to be insignificant during annealing. The strong basal texture in the starting material was observed to be weakened up to 480 mins of annealing, and on further increasing the annealing time to 1440 min, the alloy regained its basal texture. It was found that both normal and abnormal grain growth promoted basal texture during the annealing of the alloy.